Corporate health culture and employee behaviour-changing wellness practices - N. A. Grechushkina (Здоровье мегаполиса)
Introduction. Public health experts recognize that an environment that supports a culture of health best serves health goals. Therefore, some companies are creating a culture that supports health and builds healthy lifestyles for employees.Objective. A description of the key elements for creating a workplace health culture and the international experience of employers in applying corporate health practices to change employee behavior.Materials and methods. A content analysis of corporate health publications from the Scopus and PubMed bibliographic databases and public Internet sources.Discussion. Behavioral change programs aim to encourage workers to quit unhealthy habits, change-eating habits, increase physical activity, and manage stress and depression. Usually these programs implemented using a comprehensive approach. These interventions can be personal or mass-based. The former include individual counseling, food stamps or discounted fitness club memberships, systems of contracts that encourage behavioral changes in employees, rewards for quitting tobacco, free provision of anti-nicotine products, closure of company parking lots for those who live near the workplace, etc. The latter involve the introduction of a ban on smoking on the territory of the organization, reducing the cost of a healthy meal in the corporate canteen, etc.Conclusion. There is an ongoing discussion in the scientific community about the effectiveness of workplace wellness programs. Many experts agree that a comprehensive strategic approach that includes measures to create a culture of health and a supportive work environment, along with regularly updated programs to promote health and change employee behavior is beneficial to both workers and businesses.